Association of sleep quality and nap duration with cognitive frailty among older adults living in nursing homes - Siyue Liu; Zhao Hu; Yicong Guo; Feixiang Zhou; Shaojie Li; Huilan Xu (Frontiers Media S.A., 2022)
BackgroundSleep status, including sleep quality and nap duration, may be associated with frailty and cognitive impairment in older adults. Older adults living in nursing homes may be more prone to physical and cognitive frailties. This study aimed to investigate the association between sleep quality and nap duration, and cognitive frailty among older adults living in nursing homes.MethodsThis study included 1,206 older adults aged ≥ 60 years from nursing homes in Hunan province, China. A simple frailty questionnaire (FRAIL scale) was used and Mini-Mental State Examination was conducted to assess physical frailty and cognitive impairment, respectively, to confirm cognitive frailty. The Pittsburgh Sleep Quality Index was used to assess the sleep quality. Nap duration was classified as follows: no, short (≤30 min), and long (>30 min) napping. Multinomial logistic regression was conducted to estimate the odds ratio (OR) and 95% confidence interval (CI).ResultsThe prevalence of cognitive frailty among the older adults in nursing homes was 17.5%. Approximately 60.9% of the older adults had a poor sleep quality. Among the 1,206 participants, 43.9% did not take naps, 29.1% had short naps, and 26.9% had long naps. After adjusting for all covariates, poor sleep quality (OR 2.53; 95% CI 1.78-3.59; P < 0.001) and long nap duration (OR 1.77; 95% CI 1.19-2.64; P = 0.003) were associated with higher odds of cognitive frailty, but short nap duration (OR 0.60; 95% CI 0.40-0.89; P = 0.012) was associated with low prevalence of cognitive frailty.ConclusionPoor sleep quality and long nap duration are significantly associated with high risk of cognitive frailty among the older adults in nursing homes. Short nap duration was associated with low prevalence of cognitive frailty. However, these associations require further validation in older adults.Clinical trial registrationhttps://osf.io/57hv8.